Facile synthesis of Pd/PDDA-GN/PMo11Co composite and its enhanced catalytic performance for formic acid oxidation. Issue 109 (10th November 2016) - Le, Lijuan; Zhang, Xiaofeng; Ma, Ai; Zhang, Yi; Huang, Huodi; Lin, Shen
Abstract : The PMo11 Co into the composite Pd/PDDA-GN/PMo11 Co contributes to converting intermediate species CO into CO2 for formic acid oxidation. Abstract : A novel Pd-based catalyst, Pd/poly(diallyldimethylammonium chloride) functionalized graphene (PDDA-GN)/transition-metal-substituted polyoxometalate H7 PMo11 CoO40 · x H2 O (PMo11 Co), for direct formic acid fuel cells (DFAFC) has been prepared by a layer by layer (LBL) electrostatic assembly method combined with electro-deposition of Pd particles in situ . The morphology, particle size and composition of the as-prepared Pd/PDDA-GN/PMo11 Co composite were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), and energy dispersive spectroscopy (EDS). The results reveal that Pd particles are uniformly deposited on the surface of PDDA-GN/PMo11 Co. Electrochemical analysis shows that the Pd/PDDA-GN/PMo11 Co composite exhibits higher electrocatalytic activity, better electrochemical stability, and higher resistance to CO poisoning than the Pd/PDDA-GN/PMo12 and Pd/C catalysts for the formic acid oxidation reaction (FAOR). The current density of the anodic peak at the Pd/PDDA-GN/PMo12 modified electrode in the formic acid oxidation process is up to 639.3 mA mg −1, which is 4.2 times that of the Pd/C and 1.2 times that of the Pd/PDDA-GN/PMo12 . The experimental investigations indicate that PDDA-GN as a support preserves superior electric conductivity of graphene sheets of the composite, and the introduction of electroactive PMo11 Co into the composite contributes to convert intermediate species CO into CO2 . The synergistic effects of PDDA-GN and PMo11 Co remarkably enhance the electrocatalytic activity and stability of nano-Pd regarding formic acid oxidation.